Antimicrobial Resistant Salmonella enterica Typhimurium Colonizing Chickens: The Impact of Plasmids, Genotype, Bacterial Communities, and Antibiotic Administration on Resistance - Bythwood, Tameka N.; Soni, Vivek; Lyons, Karen; Hurley-Bacon, Anne; Lee, Margie D.; Hofacre, Charles; Sanchez, Susan; Maurer, John J. (Frontiers in Sustainable Food Systems, 2019)
The rise in Salmonella resistance to cephalosporins and fluoroquinolones has become a significant threat to public health. At issue, is whether agricultural use of antimicrobials is selecting antibiotic resistance in Salmonella and the degree to which large antimicrobial resistance gene reservoirs, present in animal manures, contribute to this resistance. Two in vivo studies were performed to address these questions. In the first study, chickens were administered Salmonella and commensals, including an Escherichia coli strain with a mobile, ceftiofur-resistance plasmid, in order to determine how antibiotic administration impacted resistance in E. coli and Salmonella. All antibiotics administered to chickens increased streptomycin resistance in E. coli. However, only ceftiofur administration increased resistance in Salmonella and specifically to extended-spectrum β-lactams and cephalosporins (ESBL). There was no significant increase in ESBL-resistant Salmonella in chickens administered a ceftiofur-resistance plasmid donor. In the second study, chickens were administered two different isolates of S. enterica Typhimurium and a chicken resistome to serve as a gene donor. Birds were subsequently administered chlortetracycline or streptomycin. Antimicrobial administration significantly altered aminoglycoside and tetracycline resistance in the Enterobacteriaceae population. However, there was no significant increase in antimicrobial resistant Salmonella. Administration of a chicken resistome had no significant impact on prevalence of resistance in Enterobacteriaceae populations, including Salmonella. Evident, from both studies, was that these treatments had minimal effect on increasing the prevalence of resistance in Salmonella, suggesting that other factors may be more important in dissemination of antimicrobial resistant Salmonella in chickens.